High Offerings (The Biblical archaeology review, 2020)
Some incense is higher than others. At the site of Arad in ancient Judah, archaeologists have found traces of frankincense and cannabis on two altars within an eighth-century B.C.E. temple (see reconstruction at Arad, shown here). Not only is this the earliest discovery of cannabis in southwestern Asia, but it is also the earliest […]